Age Hardening in Ultrafine-Grained Al-2 Pct Fe Alloy Processed by High-Pressure Torsion - Cubero-Sesin, Jorge (2015)
https://www.scopus.com/inward/record.url?eid=2-s2.0-84937759515&partnerID=40&md5=6c6d7635f04f5ef9de34768fe585779c